Trophic interactions among sympatric zooplanktivorous fish species in volume change conditions in a large, shallow, tropical lake - Rodrigo Moncayo-Estrada; Owen T Lind; Carlos Escalera-Gallardo (Neotropical Ichthyology)
Significant reductions in the water volume of shallow lakes impose a restriction on species segregation promoting more interactions in the trophic relationships. The diets of three closely related zooplanktivorous silversides belonging to the Atherinopsidae species flock of lake Chapala , Mexico, were analyzed at two sites (Chirostoma jordani, C. labarcae, and C. consocium). Diets were described in critical shallow (August 2000) and volume recovery conditions (August 2005). Diets included mainly cladocerans (Bosmina, Ceriodaphnia, and Daphnia) and copepods (Cyclops). A significant difference in diets was detected when comparing years (MRPP analysis, A = 0.22, p < 0.0001) and sites at different years (MRPP analysis, A = 0.17, p = 0.004). According to niche breadth mean values, species were classified as specialized and intermediate feeders. In shallow conditions, the small range of niche breadth (1.72 to 3.64) and high diet overlap values (D = 0.64, L = 8.62) indicated a high potential for interspecific exploitative interaction. When the lake volume recovered, an increase in the niche breadth range (1.04 to 4.96) and low niche overlap values (D = 0.53, L = 2.32) indicated a reduction of the species interaction. The Mann-Whitney U-test supported this pattern by showing a significant difference between years for niche overlap (p = 0.006). The increased interaction during the low volume suggests alternative segregation in life-history variations and other niche dimensions such as spatial or temporal distribution.